The Morphology and Phonology of Katajjait (Inuit Throat Games) - Bagemihl, Bruce (Canadian Journal of Linguistics/Revue canadienne de linguistique, 1988)
A linguistic theory can be considered to have explanatory force if it may be extended to a body of facts considerably beyond the domain for which it was originally conceived. In general, the further the new domain is from the original, the greater the support that accrues to that theory. In this paper, a number of developments within current morphological and phonological theory will be utilized in the analysis of an extraordinary form of vocal behaviour, the katajjait (sg. katajjaq) or throat games of the Canadian Inuit. The result will be a revealing account of the structures of these katajjait, as well as a remarkable confirmation of principles of linguistic theory from a domain which has been hitherto unreported in the linguistic literature.

The Transmission of Algonkian Indian Hymns: Between Orality and Literacy - Cavanagh, Diamond (Musical Canada: Words and Music Honouring Helmut Kallmann, 1988)